1992
DOI: 10.1139/v92-261
|View full text |Cite
|
Sign up to set email alerts
|

Thermal cyclizations of protonated poly-unsaturated aldehydes

Abstract: . Protonated 2,4-hexadienal (IH) and 2,4,6-octatrienal (2H), prepared by protonation of the analogous aldehydes in FS03H, isomerized to give cyclized products 3H and 4H at 30°C and -20°C respectively. The rate constants for the cyclization of 1H were measured in both FS03H and CF3S03H. It was found that the rate constant for isomerization decreased when CF3S03H was used as the reaction medium. It is suggested that the thermal cyclizations of 1H and 2H involve diprotonated species with protonation occurring on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Subsequently, rearrangement of the double bonds leads to the corresponding 2-alkyl-2-cyclopenten-1-one. The intermediacy of 2-alkyl-3-cyclopenten-1-one and its transformation to the thermodynamically more stable 2-alkyl-2-cyclopenten-1-one has been described before . Correspondingly, 2-methyl-2-cyclopenten-1-one was detected in some of the ( E )-2-hexenal model systems (up to 0.5%).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Subsequently, rearrangement of the double bonds leads to the corresponding 2-alkyl-2-cyclopenten-1-one. The intermediacy of 2-alkyl-3-cyclopenten-1-one and its transformation to the thermodynamically more stable 2-alkyl-2-cyclopenten-1-one has been described before . Correspondingly, 2-methyl-2-cyclopenten-1-one was detected in some of the ( E )-2-hexenal model systems (up to 0.5%).…”
Section: Resultssupporting
confidence: 52%
“…Thus, in addition to the degradation of amino acids induced by lipid oxidation products, which has been reported before by Hidalgo and co-workers, , amino-acid-induced degradations and further reactions of lipid oxidation products may be of considerable importance in thermally processed foods as well. In addition, most of the volatiles identified in this study have been reported as volatile constituents of thermally processed lipid-rich food products, ,, indicating that the mechanisms explained play a role in the formation of food volatiles.…”
Section: Resultsmentioning
confidence: 63%
See 1 more Smart Citation
“…This reaction, in an analogous fashion to the classic Nazarov transformation, involves the initial electrophilic activation of a linearly conjugated triene-carbonyl compound 8 followed by a 4πe – electrocyclization at the end of the polyene chain (Scheme , eq 1) . Depending on substrate structure, the brand new cyclopentenyl cation 10 can then lead to a cyclopentadiene product via elimination , or afford bicyclic systems such as cyclopenta­[ b ]­furans and [3.1.0]­bicyclohexenes through intramolecular nucleophilic trapping processes. Based on this synthetic strategy, we envisaged a simple and conceptually different domino protocol for the synthesis of substituted cyclopenta­[ b ]­furan-2-ones (Scheme , eq 2). The Knoevenagel condensation between dicarbonyl component Meldrum’s acid 11 and a substituted dienal 12 could afford a suitable polyunsaturated substrate for an interrupted VIN reaction providing cyclopenta­[ b ]­furan intermediate 13 as product.…”
mentioning
confidence: 99%